1998
DOI: 10.1063/1.122571
|View full text |Cite
|
Sign up to set email alerts
|

Photoluminescence and electroluminescence from copper doped zinc sulphide nanocrystals/polymer composite

Abstract: Cu-doped ZnS nanocrystals were prepared in an inverse microemulsion at room temperature as well as under a hydrothermal condition. X-ray diffraction analysis showed that the diameter of the Cu-doped ZnS nanocrystals particles was about 9 nm. These particles showed a strong photoluminescence intensity and a broad emission band from 490 to 530 nm. The half-width of emission was about 60 nm. Cu-doped ZnS nanocrystals/polymethylmethacrylate composite as a light-emitting layer was used to fabricate a single layer s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
36
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(39 citation statements)
references
References 21 publications
3
36
0
Order By: Relevance
“…For nanocrystalline ZnS:Cu only a green luminescence is reported [12][13][14][15][16], while for bulk ZnS:Cu also UV/blue, red and IR emissions are observed. The spectral position reported for the green emission in the papers on nanocrystalline ZnS:Cu varies from 425 nm [12] to 525 nm [14].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For nanocrystalline ZnS:Cu only a green luminescence is reported [12][13][14][15][16], while for bulk ZnS:Cu also UV/blue, red and IR emissions are observed. The spectral position reported for the green emission in the papers on nanocrystalline ZnS:Cu varies from 425 nm [12] to 525 nm [14].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the luminescence of nanocrystalline ZnS:Cu has been investigated [12][13][14][15][16]. Due to the large surface to volume ratio of the nanoparticles, charge carriers can be injected efficiently into these materials.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The nature of the luminescent centers responsible for the blue and green lines is ZnS was studied in sufficient detail in [11][12][13][14][15][16][17][18]. Authors [11][12][13][14][15][16][17] showed that the center responsible for the appearance of Cu green line was insulated copper ion that replaced the zinc one in the lattice of ZnS. It was determined that symmetry of this center is not less than that of the regular lattice point in cubic or hexagonal lattice of ZnS.…”
Section: Resultsmentioning
confidence: 99%
“…[11][12][13][14][15] The doped nanostructures are known to have unusual physical and chemical properties in comparison with the corresponding bulk materials. [16][17][18] Among chalcogenides, special photoelectrical and chemical properties of CdS (band gap 2.42 eV at 300 K for bulk CdS and 3.25 eV for nanosized CdS 19 ) have generated much interest because of its relatively large nonlinear response, 20 photocatalytic activity 21 and luminescence. 22 Both size and surface effects are important in nanosized materials.…”
Section: Introductionmentioning
confidence: 99%